Randomized Controlled Trial of Minimally Invasive Sacroiliac Joint Fusion Using Triangular Titanium Implants vs. NonSurgical Management for Sacroiliac Joint Dysfunction. Issue 1 (April 2016) - Polly, David W.; Cher, Daniel; Wine, Kathryn; Whang, Peter; Frank, Clay; Lockstadt, Harry; Harvey, Charles; Sembrano, Jonathan
Introduction: Sacroiliac (SI) joint dysfunction is a prevalent cause of unremitting low back pain. Does minimally invasive SIJ fusion provide superior outcomes compared with nonsurgical treatment? Methods: 148 subjects with SI joint dysfunction were randomly assigned at 19 US centers to minimally invasive SI joint fusion with triangular titanium implants ( N = 102) or nonsurgical management (NSM, n = 46). Pain, disability and quality of life scores were collected at baseline and at 1, 3, 6 and 12 months. Success rates were compared using Bayesian methods. Crossover from nonsurgical to surgical care was allowed after the 6month study visit was complete. Results: Sixmonth success rates were higher in the surgical group (81.4% versus 26.1%, posterior probability of superiority > 0.9999). Clinically important (≥15 point) ODI improvement at 6 months occurred in 73.3% of the SIJ fusion group versus 13.6% of the NSM group ( p < 0.0001). Improvements in SIJ pain and ODI were sustained at 12 months in the surgical group. Subjects who crossed over had improvements in pain, disability and quality of life similar to those in the original surgical group. Adverse events were slightly more common in the surgical group (1.3 versus 1.1 events per subject, p = 0.3063). One patient underwent immediate revision surgery for neuropathic pain related to implant malposition. 77 and 78% of subjects assigned to SIJ fusion were "very satisfied" with SIJ fusion at 6 and 12 months, respectively. Conclusions: In this study, minimally invasive SI joint fusion using triangular titanium implants was more effective than nonsurgical management at one year in relieving pain, improving function and improving quality of life in patients with SI joint dysfunction.